Knowledge, training and willingness to perform bystander cardiopulmonary resuscitation among university students in Chongqing, China: a cross-sectional study - Yan Zhang; Feng Chen; Jiani Mao; Dianguo Xing; Huixian Zhou; Ling Jia (BMJ Open)
Objective To evaluate knowledge of cardiopulmonary resuscitation (CPR) among Chinese college students and their attitude towards participating in CPR training and willingness to perform bystander CPR.Design A cross-sectional study.Participants A total of 1128 college students were selected through a multistage stratified random sampling method from 12 universities in Chongqing, China.Primary and secondary outcomes Primary outcomes included CPR knowledge and willingness to participate in training and perform bystander CPR; secondary outcomes included CPR training experience and obstacles to training and performing CPR.Results The average score on CPR knowledge was 2.078 (±1.342). Only 45.5% of the respondents were willing to participate in CPR training. Women, respondents who were postgraduate or above, with liberal arts as major and with high CPR knowledge level were more willing to participate in CPR training. A total of 47.2% of the respondents were willing to provide simple assistance, such as checking the consciousness and breathing of the patient and dialling 120 (medical emergency call). Only 34.1% indicated their willingness to perform bystander CPR on strangers. Perceived behavioural control, behavioural attitudes and subjective norms are positive predictors of willingness to provide bystander CPR.Conclusions CPR knowledge and training rate were low among Chongqing college students. Willingness to participate in training and perform bystander CPR was also low. Improving legislation, strengthening training programmes, incorporating CPR training into the school curriculum and reshaping the social and public culture of offering timely help to those in need are recommended strategies to improve bystander CPR performance.